Pyrroloquinoline quinone modulates YAP-related anti-ferroptotic activity to protect against myocardial hypertrophy - Zhou, Jiabin; Yu, Tao; Wu, Gujie; Xu, Peng; Wang, Chen; Su, Yiling; Wang, Li; Lu, Qi (Frontiers in Pharmacology, 2022)
Background: Pyrroloquinoline quinone (PQQ) has been reported to exhibit cardioprotective and antioxidant activities. Accordingly, this study was developed to explore the effects of PQQ treatment on myocardial hypertrophy and the underlying mechanism of action governing any observed beneficial effects. Methods: A transverse aortic constriction (TAC) model of myocardial hypertrophy was established in vivo using C57BL/6 mice, while neonatal murine cardiomyocytes were stimulated with phenylephrine (PE) as an in vitro validation model system. Results: Treatment of TAC model mice with PQQ significantly suppressed myocardial hypertrophy and fibrosis, in addition to inhibiting the ferroptotic death of hypertrophic myocardial cells in vivo. Subsequent in vitro analyses revealed that treatment with PQQ was sufficient to significantly alleviate PE-induced hypertrophic activity and to prevent ferroptotic induction in these primary murine cardiomyocytes. At the mechanistic level, PQQ was found to promote the upregulation of Yes-associated Protein (YAP), to suppress YAP phosphorylation, and to drive the nuclear translocation of YAP within hypertrophic cardiomyocytes. The use of a specific siRNA construct to knock down YAP expression in vitro further confirmed the ability of PQQ to protect against myocardial hypertrophy at least in part through anti-ferroptotic mechanisms. Conclusion: PQQ can regulate the pathogenesis of myocardial hypertrophy through the induction of YAP-mediated anti-ferroptotic activity, highlighting the potential value of PQQ as a novel therapeutic agent capable of slowing or preventing the progression of myocardial hypertrophy and thus delaying the onset of heart failure.